1979
DOI: 10.1051/jphys:01979004004034700
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic order effects on electric susceptibility hole mass of Sn1-x MnxTe

Abstract: To cite this version:M. Escorne, A. Mauger. Magnetic order effects on electric susceptibility hole mass of Sn1-x MnxTe. Journal de Physique, 1979, 40 (4)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…We also show that excess Te atoms in the interstitial locations lower the strength of the AFM interactions between the Mn atoms. These observations are in consistence with several experimental studies reported in the literature [1][2][3][4]. Table 6 Resistivity ρ of the RS and ZB HM compounds in units of μΩ cm, as computed by using the Kubo-Greenwood formalism.…”
Section: Summary Of Results and Conclusionsupporting
confidence: 75%
See 2 more Smart Citations
“…We also show that excess Te atoms in the interstitial locations lower the strength of the AFM interactions between the Mn atoms. These observations are in consistence with several experimental studies reported in the literature [1][2][3][4]. Table 6 Resistivity ρ of the RS and ZB HM compounds in units of μΩ cm, as computed by using the Kubo-Greenwood formalism.…”
Section: Summary Of Results and Conclusionsupporting
confidence: 75%
“…Several researchers [1][2][3][4] have carried out experimental investigation of the magnetic ordering effects in Sn 1À x Mn x Te alloys for small doping levels, x r 0:07. The structure in most cases is RS or small deviations around the RS structure.…”
Section: Comparison With Available Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The DOS of these ordered compounds at their equilibrium lattice parameters are shown in Figs. (1)(2)(3)(4). Majority and minority spin DOS are shown as spin up and down, respectively.…”
Section: A Results Of Supercell Calculations Using the Fp-lapw Methodsmentioning
confidence: 99%
“…1 In recent years, SnTe thin films doped with Mn have received some attention from experimentalists interested in the magnetic order effects such as ferromagnetism and spin glass phase, and anomalous Hall effect. [2][3][4] Recently, SnTe-based superlattices exhibited a hole mobility of 2720 cm 2 /V s, which is the highest value for any semiconductor material at room temperature was reported. 5 The doping levels of transition metals considered so far in SnTe are small, so that magnetism arises as a percolation effect among the magnetic atoms and the substance behaves as a dilute magnetic semiconductor.…”
Section: Introductionmentioning
confidence: 99%